Proyectos ecológicos : Casa L.A. - Vasquez, Fernando (1995)
Proyecto ecológico-prototipo de vivienda unifamiliar
Keywords: VIVIENDAS UNIFAMILIARES; ARQUITECTURA BIOCLIMATICA; ECOLOGIA; ESTADOS UNIDOS; CALIFORNIA; VAZQUEZ, FERNANDO